Effect of the Utilization of Non-Reciprocal Trade Preferences offered by the QUAD on Economic Growth in Beneficiary Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2021)
At the second conference of the UNCTAD in 1968, member states adopted a Resolution (Resolution 21(ii)) which stated, inter alia, that the offer of the non-reciprocal trade preferences (NRTPs) by wealthier countries to developing countries should aim to increase the export earnings of developing countries, promote their industrialization, and accelerate their rates of economic growth. The extant empirical literature has assessed whether the objectives of increasing export earnings, and promoting industrialization have been achieved, and reached mixed evidence. The present article is the first to investigate empirically whether the third goal, that is, whether NRTPs have been instrumental in promoting economic growth in beneficiary countries, has been achieved. Especially, it has examined the effect of the utilization of NRTPs (and not merely the eligibility to NRTPs) offered by the QUAD countries on the economic growth performance of beneficiary countries. It has, additionally, considered how development aid (which is another major policy tool available to wealthier countries to assist developing countries) interact with NRTPs in influencing beneficiary countries' economic growth performance. Two main blocks of NRTPs have been considered here, namely, Generalized System of Preferences (GSP) programs, and other trade preferences programs. The analysis has used a set of 90 beneficiary countries of NRTPs that are concurrently recipients of development aid, over the period 2002-2018. The two-step system generalized methods of moments is the primary estimator used to conduct the empirical analysis. Results have shown that while a higher degree of utilization of each of these two blocks of NRTPs has been associated with high economic growth rate, development aid enhances this positive effect. This highlights the need for donors to support a development strategy based on the provision of both development aid and NRTPs, if they were to help beneficiary countries to promote economic growth.
Keywords: F13; F43; F35; O10; 330; Utilization of non-reciprocal trade preferences; Economic Growth; QUAD countries; Developing Countries